Obtenção e caracterização bioquímica de xilanases nativas e recombinante do fungo Leucoagaricus gongylophorus - Moreira, Ariele Cristina (Universidade Federal de São Carlos, 2013)
Xylanases are enzymes which randomly cleave the main chain of xylan, the most abundant non-cellulosic polysaccharide of plants cell wall. Xylanases are commonly produced by a wide range of organisms including bacteria, algae, fungi, protozoa, and certain herbivorous insects and crustaceans also produce xylanases. Leucoagaricus gongylophorus, a mutualistic fungus of leafcutting ant Atta sexdens, secretes enzymes with xylanolytic activity and the gene encoding a xylanase was recently identified. In this work the xylanolytic profile of L. gongylophorus was studied and two enzymes with xylanolytic activity (XyLg1 and XyLg2) were isolated, purified and characterized. XyLg1 has a molecular mass of about 38kDa and pI greater than 4.8. For beechwood xylan substrate XyLg1 showed optimum temperature of 40 °C, optimum pH between 8.5 to 10.5 and Km =14, 7 ± 7.6 mg.ml-1. Due to these features XyLg1 may be used in processes such as bio-bleaching pulp. XyLg1 was also analyzed by mass spectrometry technique being associated with a polygalacturonase of the same fungus. Kinetic studies of the XyLg1 using polygalacturonic acid as substrate were developed (optimum pH= 5.5, optimum temperature between 50 and 60 ° C and Km= 2.2 ± 0.5 mg.ml-1). XyLg2 has molecular weight of about 24kDa and pI less than 4.8, and thus it is an acid protein. Parameter such as optimum temperature (70 °C) and pH (4.0) as well as the kinetic parameters (Km 7.4 ± 2.0 mg.ml-1) using beechwood xylan as substrate were determined for XyLg2. This enzyme exhibits desirable characteristics for improving animal feed, for example. LgXyn2 shows no activity with polygalacturonic acid. For the purpose of producing larger amount of xylanase from the L. gongylophorus the gene sequence encoding a xylanase (LgXyn1, GenBank: EF208066.1) was used to synthesize forward and reverse primers and was possible to amplify a different gene (xyl) that encodes the synthesis of a new xylanase called here LgXyn2. The gene was cloned into pETSUMO vector and the recombinant expressed in E.coli has no activity even when histidine tail (fusion) is removed with Sumo protease. These results suggest that the glycosylation is an important factor for xylanolitic activity. Then the xyl gene was cloned into pPICZalphaA vector and LgXyn2 was expressed in P. pastoris, secreted into the extracellular medium and the enzyme has xylanolitic activity. This result showed that the new gene (xyl) encodes a functional enzyme and that P. pastoris is a efficient system to obtain the active enzyme.
Obtention and biochemical characterization of native and recombinant xylanases from Leucoagaricus gongylophorus fungus
Keywords: Química orgânica; Bioquímica; Biologia molecular; Xilanase; Fungos; Proteínas; Purificação de enzimas nativas; Caracterização enzimática; Expressão heteróloga de proteínas; Xylanase; Native enzyme purification; Enzymatic characterization; Heterologous expression; CIENCIAS EXATAS E DA TERRA::QUIMICA